2022
DOI: 10.3390/en15103829
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Overheating Risk for Typical Dwellings and Passivhaus in the UK

Abstract: There is growing concern that airtight and well-insulated buildings designed to limit heat loss in temperate and cold climates could unintentionally elevate the risk of overheating in summers. Existing literature primarily uses dynamic simulation to investigate this problem due to the difficulty of obtaining large-scale in-performance data. To address this gap, we undertake a meta-analysis of large-scale indoor air temperature data for 195 UK dwellings, as a study of performance in a temperate climate. Of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…Post-occupancy, most experienced the homes as warm and comfortable, although for some, thermal comfort was still a concern. Similar to findings of quantitative research by Baba et al (2022) [54] and Jang et al (2022) [55], many of our participants explained how their homes had been excessively warm over summer months. However, unlike Jang et al (2022) [55], our participants explained that they had experienced difficulty in reducing the temperature, and naturally ventilating the home did not suffice.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Post-occupancy, most experienced the homes as warm and comfortable, although for some, thermal comfort was still a concern. Similar to findings of quantitative research by Baba et al (2022) [54] and Jang et al (2022) [55], many of our participants explained how their homes had been excessively warm over summer months. However, unlike Jang et al (2022) [55], our participants explained that they had experienced difficulty in reducing the temperature, and naturally ventilating the home did not suffice.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to findings of quantitative research by Baba et al (2022) [54] and Jang et al (2022) [55], many of our participants explained how their homes had been excessively warm over summer months. However, unlike Jang et al (2022) [55], our participants explained that they had experienced difficulty in reducing the temperature, and naturally ventilating the home did not suffice. This had reportedly caused discomfort and necessitated the purchase of cooling appliances at additional cost and energy consumption.…”
Section: Discussionsupporting
confidence: 88%
“…Although several studies have been undertaken on summertime overheating in dwellings [16][17][18][19], the focused has largely been on newly built housing. A recent study on the extent of overheating in existing UK dwellings found that a high proportion of dwellings failed to meet the UK Approved Document Part O on overheating in newly built homes [20].…”
Section: Evidence To Datementioning
confidence: 99%